CONFIDENCE treatment success: long-term real-world effectiveness and safety of ocrelizumab in Germany - Buttmann, Mathias; Weber, Martin S.; Meuth, Sven G.; Blümich, Sandra; Hieke-Schulz, Stefanie; Dirks, Petra; Eggebrecht, Julius C.; Ziemssen, Tjalf (Frontiers in Neurology, 2025)
BackgroundEarly high-efficacy treatment for people with relapsing multiple sclerosis (pwRMS) may provide better long-term outcomes compared with the escalation strategy. In this study, we present an analysis of treatment success and safety from the CONFIDENCE study in a real-world cohort of pwRMS treated with ocrelizumab in different treatment lines for up to 5.5 years.MethodsThe ongoing German non-interventional post-authorization safety study, CONFIDENCE (ML39632, EUPAS22951), evaluates the long-term safety and effectiveness of therapy in pwMS newly treated with ocrelizumab or other disease-modifying therapies for up to 10 years. This analysis presents CONFIDENCE treatment success (proportion of people with no clinical disease activity measured by relapse or disease progression and no treatment discontinuation due to adverse event [AE] or lack of therapeutic effectiveness), confirmed disability progression (CDP), annualized relapse rates, and safety in pwRMS stratified by the number of previous MS therapies (PMSTs).ResultsAt the data cutoff (11 October 2023), the full analysis set included 2,261 pwRMS treated with ≥1 dose of ocrelizumab. At baseline, the mean age (SD) of the participants was 41.16 (11.39) years (treatment-naïve, 39.19 [12.95] years; ≥3 PMSTs, 42.80 [10.08] years), and the mean Expanded Disability Status Scale (EDSS) score was 3.08 (1.86) (treatment-naïve, 2.37 [1.54]; ≥3 PMSTs, 3.57 [1.90]). Overall, 58.4% of pwRMS with continuous treatment achieved CONFIDENCE treatment success from baseline until year 5 (74.0 and 50.3% of pwRMS with 0 and ≥3 PMSTs). The main reasons for not achieving CONFIDENCE treatment success were relapse and CDP, while treatment discontinuation due to AEs or lack of effectiveness played a minor role. The proportion of pwRMS with AEs did not increase with longer treatment duration and tended to be higher with more PMSTs. The spectrum of AEs was similar across treatment lines, and no new or unexpected AEs were observed.ConclusionCONFIDENCE treatment success remained high over 5 years of ocrelizumab treatment, even among people with RMS (pwRMS) with a higher number of PMSTs. Only a small proportion of pwRMS discontinued treatment due to AEs. These results support early intervention with high-efficacy ocrelizumab treatment to optimize long-term outcomes for pwRMS.Trial registrationhttps://catalogues.ema.europa.eu/node/3142/administrative-details, identifiers ML39632 and EUPAS22951.